Ungoverned Territories - Rabasa, Angel; Boraz, Steven; Chalk, Peter; Cragin, Kim; Karasik, Theodore W. (RAND Corporation, 2023)
Using a two-tiered framework areas applied to eight case studies from around the globe, the authors of this ground-breaking work seek to understand the conditions that give rise to ungoverned territories and make them conducive to a terrorist or insurgent presence. They also develop strategies to improve the U.S. ability to mitigate their effects on U.S. security interests.